Enhancing the knowledge and skills of health cadres and mothers to prevent developmental disorders through stimulation interventions - Ningsih Jaya; Ambo Dalle; Sri Anggriani (PAGEPress Publications, 2024)
The golden age of toddlerhood is a crucial time for growth and development that requires special attention. Failure to support children during this time can cause developmental issues that affect their future growth. This study examined whether toddler growth and development interventions prevent developmental disorders. This pre-experimental study used a one-group pre-test/post-test design. The proportional random sample included 70 participants. The respondents' age, occupation, education, use of toddler growth and development stimulation interventions, and health cadres' and mothers' knowledge and skills were variables. Data were analyzed using Wilcoxon and Mann-Whitney. There was a significant increase in health cadres and mothers' knowledge and skills for promoting toddler growth and preventing developmental disorders (P=0.000<0.05). Effective toddler growth and development interventions improve health cadres and mothers' knowledge and skills, preventing developmental disorders in toddlers. These findings suggest that targeted educational programs for health cadres and mothers may reduce developmental disorders and promote healthier growth trajectories for children.